Influence of Solvent Polarity on Color Intensity of Marigold Flower Extracts - Retnowati, Rurini; Sulistyarti, Hermin; Suratmo; Ulfa, Siti Mariyah; Kamulyan, Budi; Destiara, Irena Amelia; Muzdhalifa, Sefira Putri; Ananda, Regina Ridha (ALKIMIA, 2026)
In this paper, we report research on the extraction of natural dyes from yellow and orange marigold (Tagetes erecta L.) petals using different solvents. This research aims to determine the optimal dye removal process, investigate stability, and establish color intensity profiles. In order to extract natural dyes that produced various shades of the dried powder of yellow and orange marigold flower petals, two solvents with different polarities, n-hexane and ethyl acetate were used. The maceration procedure using different solvent types was carried out separately. The stability study revealed that all the dyes at room temperature showed better stability with minor changes observed by UV-Visible (UV-Vis) spectrum profiles, indicating that the extracts were stable until the 30th day. To ascertain the color intensity profiles, analytical tests such as UV-Vis spectroscopy and colorimetry utilizing a color reader device were carried out. The color intensity profile of the yellow and orange marigold flower extracts resulting from the UV-Vis spectrum analysis showed that the absorption of the ethyl acetate extract is higher. The pigment concentration, which is also expressed by absorbance, is connected to variations in color intensity. Additionally, the color intensity profile characterization using a color reader revealed that the n-hexane and ethyl acetate extracts had different Commission Internationale d'Eclairage (CIE) L*, a*, and b* values. The yield and color intensity of the extracts were affected by the solvent polarity. In conclusion, the study of the extract's color intensity profile using UV-Vis spectroscopy and a color reader shows that the intensity parameters are aligned.